Australia on display: Tracing an Australian identity through the evolving costume design for The Australian Ballet's production The Display. Issue 1 (1st June 2017) - Collett, Emily; Alsop, Roger
The topic of costume for performance as a marker of national identity is in its infancy within the context of theatre studies. As the means by which an audience relates to character and narrative, costume is central to our understanding of identity. Here, we consider costume for performance, specifically for dance, in Australia as an indicator of the developing national identity, using the 1964, 1983 and 2012 Australian Ballet productions of The Display as a case study. The original 1964 costumes were credited to expatriate artist Sidney Nolan, the 1983 version was designed by Sydney fashion designer Adele Weiss and the 2012 remount utilized photographs, written documentation and memories to recreate the original 1964 costumes. By examining the three sets of costumes, we aim to demonstrate how a study of the costumed body offers insights into Australia's evolving national character.